2015
DOI: 10.1108/ijph-10-2014-0037
|View full text |Cite
|
Sign up to set email alerts
|

Emotional distress and sense of coherence in women completing a motivational program in five countries. A prospective study

Abstract: For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…More recent research shows three additional countries: Austria (Mautner et al, 2014), Estonia (Höjdahl, Magnus, Mdala, Hagen, & Langeland, 2015), and Malaysia (Rostami, Lamit, Khoshnava, & Rostami, 2014).…”
Section: The Validity and Reliability Of The Sense Of Coherencementioning
confidence: 99%
“…Despite SOC developing during adolescence, studies have reported that SOC (and reductions in re-offending) can increase following intervention with adult men (Lindblom et al 2018). Furthermore, in a study of incarcerated women, increased SOC related to a significant decrease in global emotional distress (Höjdahl et al 2015). Therefore, SOC appears to have strong grounding for subsequent intervention work in these at-risk populations.…”
Section: Discussionmentioning
confidence: 98%